Effect of osmotic blood-brain barrier disruption on gentamicin penetration into the cerebrospinal fluid and brains of normal rabbits. - Strausbaugh, L J (1983)
Rapid infusion of hyperosmolar solutions into the internal carotid artery transiently disrupts the blood-brain barrier, permitting entry of substances that are ordinarily excluded from the nervous system. This study compared gentamicin concentrations in the cerebrospinal fluid (CSF) and brain tissue of rabbits receiving intracarotid infusions of 2 molal mannitol with those in three groups of control animals. After catheter placement and intravenous gentamicin administration (20 mg/kg), rabbits received either 2 molal mannitol in the internal carotid artery, 2 molal mannitol intravenously, 0.9% saline in the internal carotid artery, or 0.9% saline intravenously. Mannitol and saline were administered in 8-ml bolus injections over 40 s. After 2 h, serum, CSF, and brain specimens were obtained for antibiotic assay. Gentamicin concentrations in serum were comparable in all groups (mean concentrations ranged from 14.6 to 17.9 micrograms/ml at 60 min and from 5.7 to 7.4 micrograms/ml at 135 min), but gentamicin concentrations in CSF and brains were significantly higher in animals in the group receiving mannitol in the internal carotid artery. In this group the mean gentamicin concentration in CSF, 5.3 micrograms/ml, was twofold greater than those in the other three groups (range, 1.7 to 2.6 micrograms/ml). Similarly, the mean gentamicin concentration in the brains of animals in the group receiving mannitol in the internal carotid artery, 2.3 micrograms/g was significantly higher than those in the other groups (mean of measurable values, 1.4 micrograms/g, in all three control groups). Osmotic disruption of the blood-brain barrier enhanced the penetration of gentamicin into CSF and brain tissue.